Composite solid electrolyte, all-solid-state lithium battery and preparation method of all-solid-state lithium battery

By using the composite solid electrolyte of xLi2O·TaCl5·yBaTiO3 in lithium-ion batteries, the lithium dendrites problem is solved, the cycle stability and safety performance of the battery are improved, and the effects of high energy density and long cycle life are achieved.

CN119695258APending Publication Date: 2025-03-25HUNAN LIFANG NEW ENERGY SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411829999.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Composite solid electrolytes have lithium dendrites problems in lithium-ion batteries, resulting in reduced battery cycle life and safety problems.

Method used

The composite solid electrolyte of xLi2O·TaCl5·yBaTiO3 is used to improve the ionic conductivity through the combination of amorphous chloride and barium titanate, and the growth direction of dendrites is changed through the piezoelectric effect of BaTiO3 to inhibit the formation of continuous dendrites.

Benefits of technology

It effectively inhibits the formation of lithium dendrites, improves the cycle stability and safety performance of the battery, has an energy density of no less than 330Wh/kg, and the capacity retention rate is no less than 90% after 100 weeks of circulation, and does not catch fire during the acupuncture experiment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695258A_ABST
    Figure CN119695258A_ABST
Patent Text Reader

Abstract

The invention discloses a composite solid electrolyte, an all-solid-state lithium battery and a preparation method of the all-solid-state lithium battery. The general formula of the composite solid electrolyte is xLi2O.TaCl5.yBaTiO3, x is larger than or equal to 1 and smaller than or equal to 2, y is larger than or equal to 0.1 and smaller than or equal to 1, the composite solid electrolyte comprises amorphous chloride and barium titanate, the amorphous chloride can improve the ionic conductivity, the ionic conductivity can be further improved by adding the barium titanate, the piezoelectric effect of the barium titanate can change the dendritic crystal growth direction, continuous dendritic crystals are not formed, and therefore battery short circuit caused by the dendritic crystals is restrained, and the service life of the battery is prolonged. When the material is applied to the all-solid-state lithium battery, the cycling stability can be effectively improved, and the cycling stability of the all-solid-state lithium battery can be further improved by combining the lithium phosphotungstate modified lithium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state lithium batteries, and in particular relates to a composite solid-state electrolyte, an all-solid-state lithium battery and a preparation method thereof. Background Art

[0002] With the advancement of the country's "dual carbon" goals, an energy revolution has been launched in the transportation field, and the popularity of electric vehicles has increased rapidly. Among on-board power batteries, lithium-ion batteries dominate. Currently, commercial lithium-ion batteries generally use liquid organic electrolytes, which are prone to combustion when the battery thermally runs away, causing safety accidents. Even lithium iron phosphate-based batteries cannot completely avoid safety issues. An effective way to solve battery safety problems is to use solid electrolytes instead of organic liquid electrolytes to assemble all-solid-state batteries.

[0003] However, the electrochemical window of solid electrolytes is relatively narrow, and oxidation reactions are likely to occur at the positive electrode or reduction reactions at the negative electrode. Interface side reactions lead to large interface resistance, which is not conducive to interface charge transfer, causing battery performance degradation and eventual failure. Solid electrolytes also face the problem of lithium dendrites, which can cause battery short circuits, resulting in reduced battery cycle life and safety issues. Summary of the invention

[0004] The purpose of the present invention is to provide a composite solid electrolyte to overcome the lithium dendrite problem existing in the above-mentioned composite solid electrolyte, which leads to defects or shortcomings such as reduced battery cycle life and safety issues.

[0005] Another object of the present invention is to provide a method for preparing the composite solid electrolyte.

[0006] Another object of the present invention is to provide an all-solid-state lithium battery.

[0007] Another object of the present invention is to provide a method for preparing the all-solid-state lithium battery.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A composite solid electrolyte, wherein the general formula of the composite solid electrolyte is xLi2O·TaCl5·yBaTiO3, wherein 1≤x≤2, 0.1≤y≤1.

[0010] The present invention provides a composite solid electrolyte, which includes amorphous chloride and barium titanate. The amorphous chloride can improve the ionic conductivity. The addition of BaTiO3 can further improve the ionic conductivity. Its piezoelectric effect can change the growth direction of dendrites and prevent the formation of continuous dendrites, thereby inhibiting battery short circuit caused by dendrites.

[0011] It should be noted that the general formula of the composite solid electrolyte described in the present invention is xLi2O·TaCl5·yBaTiO3, wherein 1≤x≤2, 0.1≤y≤1; x can specifically be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, or a range between any of the above values; y can specifically be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, or a range between any of the above values.

[0012] Furthermore, 1.4≤x≤1.8.

[0013] Furthermore, the preparation method of the composite solid electrolyte comprises the following steps:

[0014] It is prepared by ball milling Li2O, BaTiO3 and TaCl5.

[0015] In some preferred embodiments, the ball milling time is 5 to 20 hours; the ball milling speed is 300 to 600 rpm.

[0016] The present invention also provides an all-solid-state lithium battery, comprising the composite solid-state electrolyte.

[0017] In some preferred specific embodiments, it also includes a negative electrode, an intermediate layer and a positive electrode; the negative electrode is a lithium alloy, and the intermediate layer is lithium phosphotungstate.

[0018] Through experimental research, the inventors found that using lithium alloy as the negative electrode can improve the interface stability with the composite solid electrolyte and inhibit lithium dendrites compared to pure metallic lithium negative electrode. Using lithium phosphotungstate as the intermediate layer has better interface stability with the lithium alloy, which can further inhibit the interface reaction between the composite solid electrolyte and the lithium alloy and improve the cycle stability of the battery.

[0019] Furthermore, the lithium alloy includes one or more of lithium silicon alloy, lithium carbon alloy, lithium silver alloy, lithium boron alloy, lithium tin alloy, lithium magnesium alloy or lithium zinc alloy.

[0020] In some preferred embodiments, the lithium alloy is generally present in the form of lithium alloy foil.

[0021] In some preferred embodiments, the lithium alloy is prepared by a melting method.

[0022] Specifically, it can be prepared by the following preparation method:

[0023] The metal lithium is heated to above the melting point in an inert atmosphere, and then other substances are added, followed by cooling and rolling to obtain the product.

[0024] Specifically, the other substances include one or more of silicon, carbon, silver, boron, tin, magnesium or zinc.

[0025] Specifically, the molar content of lithium in the lithium alloy is 20 to 90%.

[0026] Furthermore, the structural formula of the lithium phosphotungstate is Li n PW 12 O 40 , wherein 2≤n≤3, for example but not limited to 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3, or a range between any of the above values.

[0027] In some preferred embodiments, the Li n PW 12 O 40 By H3PW 12 O 40 Obtained by hydrothermal reaction of mH2O and LiCl.

[0028] The present invention does not impose any special limitation on m, i.e. H3PW 12 O 40 ·mH2O only needs the presence of water of crystallization.

[0029] In some preferred embodiments, m is 20-40.

[0030] Specifically, the temperature of the hydrothermal reaction is 50 to 90° C., and the time of the hydrothermal reaction is 2 to 10 hours.

[0031] In some preferred embodiments, the Li n PW 12 O 40 The ionic conductivity is 1×10 -4 S / cm~1×10 -3 S / cm. Within this range, the comprehensive performance of the prepared all-solid-state lithium battery is significantly improved.

[0032] In some preferred embodiments, the thickness of the lithium alloy is 10-100 μm. Within this range, both the cycle life and energy density of the battery can be achieved.

[0033] In some preferred embodiments, the thickness of the lithium phosphotungstate is 1 to 10 μm. Within this range, the reaction between the lithium alloy and the composite solid electrolyte can be better suppressed, the formation of lithium dendrites can be suppressed, and the cycle life and energy density of the battery can be improved.

[0034] In some preferred embodiments, the thickness of the composite solid electrolyte is 10 to 100 μm. Within this range, the lithium ion transport performance, mechanical strength, and battery energy density can be better balanced, and the growth of lithium dendrites can be effectively inhibited.

[0035] The present invention also provides a method for preparing an all-solid-state battery, comprising the following steps:

[0036] S1. Pressing lithium phosphotungstate onto the surface of a lithium alloy to obtain a surface-modified lithium alloy negative electrode;

[0037] The composite solid electrolyte and the binder are mixed evenly by dry method, and the composite solid electrolyte membrane is obtained by roller pressing;

[0038] The positive electrode active material, the binder, the conductive agent and the solid electrolyte are mixed evenly by dry method, and the positive electrode film is obtained by roller pressing;

[0039] S2. The positive electrode film, the composite solid electrolyte membrane and the surface-modified lithium alloy negative electrode are pressed in sequence, and aluminum foil and copper foil are placed on the positive and negative electrode sides respectively, and an all-solid-state lithium battery is obtained after packaging.

[0040] Specifically, the composite solid electrolyte membrane is pressed onto the lithium phosphotungstate surface of the surface-modified lithium alloy negative electrode.

[0041] The binder in the present invention can be selected from commonly used binders, such as but not limited to one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer or polyperfluoroethylenepropylene.

[0042] More preferably, the binder is polytetrafluoroethylene, which can be fiberized to form a three-dimensional link network, better bond the positive electrode active material, the conductive agent and the composite solid electrolyte, and facilitate film formation.

[0043] The positive electrode active material of the present invention can be selected from commonly used positive electrode active materials, such as but not limited to one or more of spinel lithium manganese oxide, spinel nickel lithium manganese oxide, lithium manganese phosphate, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt phosphate, lithium vanadium phosphate, lithium cobalt oxide, layered oxide or lithium-rich manganese-based materials.

[0044] The conductive agent of the present invention can be selected from commonly used conductive agents, such as but not limited to one or more of acetylene black, Super P, nanocarbon tubes or nanocarbon fibers.

[0045] Furthermore, the solid electrolyte in step S1 is a composite solid electrolyte B.

[0046] Furthermore, the composite solid electrolyte B and the composite solid electrolyte have the same composition.

[0047] In some preferred specific embodiments, the mass ratio of the positive electrode active material, the binder, the conductive agent, and the solid electrolyte in the positive electrode film is (70-90):(0.1-5):(1-10):(1-20).

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The present invention provides a composite solid electrolyte, which improves ionic conductivity through amorphous compounds, and the addition of BaTiO3 can further improve ionic conductivity. Its piezoelectric effect can change the growth direction of dendrites, and continuous dendrites are not formed, thereby inhibiting battery short circuit caused by dendrites; the present invention also provides an all-solid-state lithium battery, in which lithium alloy is used as the negative electrode, and lithium phosphotungstate is combined on the surface to effectively improve the interface stability of lithium alloy and composite solid electrolyte, and inhibit lithium dendrites. The composite solid electrolyte has high-voltage resistance, is compatible with the positive electrode, can effectively inhibit interface reactions, and inhibit lithium dendrites. The all-solid-state lithium battery has good energy density, cycle performance and safety performance, the energy density is not less than 330Wh / kg, and the needle puncture test does not catch fire, and the capacity retention rate after 100 cycles is not less than 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is a schematic diagram of the structure of an all-solid-state lithium battery;

[0051] Figure 2 This is a charge and discharge curve diagram of the all-solid-state lithium battery prepared in Example 5;

[0052] Figure 3 This is a cycle life diagram of the all-solid-state lithium battery prepared in Example 5;

[0053] Figure 4 This is the cycle life diagram of the all-solid-state lithium battery prepared in Comparative Example 7. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0055] Example 1

[0056] A composite solid electrolyte is prepared by the following preparation method:

[0057] Li2O, BaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1.6:0.2:1. 1.6Li2O·TaCl5·0.2BaTiO3 was prepared by ball milling. The ball milling time was 10 hours and the ball milling speed was 450 rpm.

[0058] Example 2

[0059] A composite solid electrolyte is prepared by the following preparation method:

[0060] Li2O, BaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1.5:0.3:1. 1.5Li2O·TaCl5·0.3BaTiO3 was prepared by ball milling. The ball milling time was 8 hours and the ball milling speed was 500 rpm.

[0061] Example 3

[0062] A composite solid electrolyte is prepared by the following preparation method:

[0063] Li2O, BaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1.7:0.1:1. 1.7Li2O·TaCl5·0.1BaTiO3 was prepared by ball milling. The ball milling time was 12 hours and the ball milling speed was 480 rpm.

[0064] Example 4

[0065] A composite solid electrolyte is prepared by the following preparation method:

[0066] Li2O, BaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1:1:1. Li2O·TaCl5·BaTiO3 was prepared by ball milling. The ball milling time was 15 hours and the ball milling speed was 550 rpm.

[0067] Comparative Example 1

[0068] A composite solid electrolyte is prepared by the following preparation method:

[0069] Li2O and TaCl5 were used as precursors and mixed at a molar ratio of 1.6:1. 1.6Li2O·TaCl5 was prepared by ball milling. The ball milling time was 10 hours and the ball milling speed was 450 rpm.

[0070] Comparative Example 2

[0071] A composite solid electrolyte is prepared by the following preparation method:

[0072] Li2O, BaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1.6:0.03:1. 1.6Li2O·TaCl5·0.03BaTiO3 was prepared by ball milling. The ball milling time was 10 hours and the ball milling speed was 450 rpm.

[0073] Comparative Example 3

[0074] A composite solid electrolyte is prepared by the following preparation method:

[0075] Li2O, BaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1.6:1.2:1. 1.6Li2O·TaCl5·1.2BaTiO3 was prepared by ball milling. The ball milling time was 10 hours and the ball milling speed was 450 rpm.

[0076] Comparative Example 4

[0077] A composite solid electrolyte is prepared by the following preparation method:

[0078] Li2O, BaTiO3 and NbCl5 were used as precursors and mixed in a molar ratio of 1.6:0.2:1. 1.6Li2O·NbCl5·0.2BaTiO3 was prepared by ball milling. The ball milling time was 10 hours and the ball milling speed was 450 rpm.

[0079] Comparative Example 5

[0080] A composite solid electrolyte is prepared by the following preparation method:

[0081] LiCl, BaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1.6:0.2:1. 1.6LiCl·TaCl5·0.2BaTiO3 was prepared by ball milling. The ball milling time was 10 hours and the ball milling speed was 450 rpm.

[0082] Comparative Example 6

[0083] A composite solid electrolyte is prepared by the following preparation method:

[0084] Li2O, CaTiO3 and TaCl5 were used as precursors and mixed in a molar ratio of 1.6:0.2:1. 1.6Li2O·TaCl5·0.2CaTiO3 was prepared by ball milling. The ball milling time was 10 hours and the ball milling speed was 450 rpm.

[0085] Example 5

[0086] An all-solid-state lithium battery is prepared by the following preparation method:

[0087] S1. Li3PW 12 O40 The surface of the lithium-magnesium alloy foil was pressed to obtain a surface-modified lithium-magnesium alloy negative electrode; the composite solid electrolyte and polytetrafluoroethylene described in Example 1 were mixed uniformly in a mass ratio of 100:3, and a self-supporting 1.6Li2O·TaCl5·0.2BaTiO3 film (composite solid electrolyte film with a thickness of 40 μm) was obtained by shearing, dispersing and rolling; the commercial LiNi 0.85 Co 0.05 Mn 0.1 O2 material, polytetrafluoroethylene, acetylene black, and 1.6Li2O·TaCl5·0.2BaTiO3 were mixed in a weight ratio of 82:2:3:13, and a positive electrode film (thickness of 90 μm) was obtained by shear dispersion and roller pressing;

[0088] The Li3PW 12 O 40 H3PW 12 O 40 ·30H2O and LiCl are used as raw materials, and are obtained by hydrothermal reaction at 80°C and vacuum drying, with a thickness of 4μm; the lithium-magnesium alloy foil is obtained by melting, cooling and rolling metal magnesium and lithium as raw materials, wherein the lithium molar content of the lithium-magnesium alloy foil is 80% and the thickness is 40 microns;

[0089] S2. The positive electrode film, the composite solid electrolyte membrane and the surface-modified lithium-magnesium alloy negative electrode are Figure 1 The structure shown is pressed in sequence (the composite solid electrolyte membrane is pressed on the lithium phosphotungstate surface of the surface-modified lithium alloy negative electrode), and aluminum foil and copper foil collectors are placed on the positive and negative electrode sides respectively, and after isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0090] Example 6

[0091] An all-solid-state lithium battery is prepared by the following preparation method:

[0092] S1. Li3PW 12 O 40 The surface of the lithium-zinc alloy foil was pressed to obtain a surface-modified lithium-zinc alloy negative electrode; the composite solid electrolyte and polytetrafluoroethylene described in Example 2 were mixed uniformly in a mass ratio of 100:2, and a self-supporting 1.5Li2O·TaCl5·0.3BaTiO3 film (composite solid electrolyte film with a thickness of 50 μm) was obtained by shearing, dispersing and rolling; the commercial LiFe 0.3 Mn 0.7 PO4 material, polytetrafluoroethylene, Super P, and 1.5Li2O·TaCl5·0.3BaTiO3 were mixed in a weight ratio of 82.5:1.5:5:11, and a positive electrode film (thickness of 80 μm) was obtained by shear dispersion and roller pressing;

[0093] The Li3PW 12 O 40 H3PW 12 O 40 ·30H2O and LiCl are used as raw materials, and are obtained by hydrothermal reaction at 80°C and vacuum drying, with a thickness of 3μm; the lithium-zinc alloy foil is obtained by melting, cooling and rolling metal zinc and lithium as raw materials, wherein the lithium molar content of the lithium-zinc alloy foil is 70% and the thickness is 50 microns;

[0094] S2. The positive electrode film, the composite solid electrolyte membrane and the surface-modified lithium-zinc alloy negative electrode are Figure 1 The structure shown is pressed in sequence (the composite solid electrolyte membrane is pressed on the lithium phosphotungstate surface of the surface-modified lithium alloy negative electrode), and aluminum foil and copper foil collectors are placed on the positive and negative electrode sides respectively, and after isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0095] Example 7

[0096] An all-solid-state lithium battery is prepared by the following preparation method:

[0097] S1. Li3PW 12 O 40 The surface of the lithium-silver alloy foil was pressed to obtain a surface-modified lithium-silver alloy negative electrode; the composite solid electrolyte and polytetrafluoroethylene described in Example 3 were mixed uniformly in a mass ratio of 100:1.5, and a self-supporting 1.7Li2O·TaCl5·0.1BaTiO3 film (composite solid electrolyte film with a thickness of 50 μm) was obtained by shearing, dispersing and rolling; the commercial Li 1.2 Ni 0.2 Mn 0.6 O2 material, polytetrafluoroethylene, carbon nanotubes, and 1.7Li2O·TaCl5·0.1BaTiO3 were mixed at a weight ratio of 83.5:1.5:5:10, and a positive electrode film (thickness of 90 μm) was obtained by shear dispersion and roller pressing;

[0098] The Li3PW 12 O 40 H3PW 12 O 40 30H2O and LiCl are used as raw materials, and are obtained by hydrothermal reaction at 80°C and vacuum drying, with a thickness of 5μm; the lithium-silver alloy foil is obtained by melting, cooling and rolling metal silver and lithium as raw materials, wherein the lithium molar content of the lithium-silver alloy foil is 75% and the thickness is 50 microns;

[0099] S2. The positive electrode film, the composite solid electrolyte membrane and the surface-modified lithium-silver alloy negative electrode are Figure 1The structure shown is pressed in sequence (the composite solid electrolyte membrane is pressed on the lithium phosphotungstate surface of the surface-modified lithium alloy negative electrode), and aluminum foil and copper foil collectors are placed on the positive and negative electrode sides respectively, and after isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0100] Example 8

[0101] An all-solid-state lithium battery is prepared by the following preparation method:

[0102] S1. Li3PW 12 O 40 The surface of the lithium-tin alloy foil was pressed to obtain a surface-modified lithium-tin alloy negative electrode; the composite solid electrolyte described in Example 4 and polytetrafluoroethylene were mixed uniformly in a mass ratio of 100:2, and a self-supporting Li2O·TaCl5·BaTiO3 film (composite solid electrolyte film with a thickness of 60 μm) was obtained by shearing, dispersing and rolling; the commercial LiNi 0.8 Co 0.1 Mn 0.1 O2 material, polytetrafluoroethylene, nanocarbon fiber, and 1.6Li2O·TaCl5·BaTiO3 were mixed in a weight ratio of 83:1.5:4:11.5, and a positive electrode film (thickness of 90 μm) was obtained by shear dispersion and roller pressing;

[0103] The Li3PW 12 O 40 H3PW 12 O 40 ·30H2O and LiCl are used as raw materials, and are obtained by hydrothermal reaction at 80°C and vacuum drying, with a thickness of 4μm; the lithium-tin alloy foil is obtained by melting, cooling and rolling metal tin and lithium as raw materials, wherein the lithium molar content of the lithium-tin alloy foil is 85% and the thickness is 60 microns;

[0104] S2. The positive electrode film, the composite solid electrolyte membrane and the surface-modified lithium-tin alloy negative electrode are Figure 1 The structure shown is pressed in sequence (the composite solid electrolyte membrane is pressed on the lithium phosphotungstate surface of the surface-modified lithium alloy negative electrode), and aluminum foil and copper foil collectors are placed on the positive and negative electrode sides respectively, and after isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0105] Comparative Example 7

[0106] The preparation method and steps are the same as those of Example 5, except that an equal amount of the composite solid electrolyte in Comparative Example 1 is used instead of the composite solid electrolyte in Example 1.

[0107] Comparative Example 8

[0108] The preparation method and steps are the same as those of Example 5, except that an equal amount of the composite solid electrolyte in Comparative Example 2 is used instead of the composite solid electrolyte in Example 1.

[0109] Comparative Example 9

[0110] The preparation method and steps are the same as those of Example 5, except that an equal amount of the composite solid electrolyte in Comparative Example 3 is used instead of the composite solid electrolyte in Example 1.

[0111] Comparative Example 10

[0112] The preparation method and steps are the same as those of Example 5, except that an equal amount of the composite solid electrolyte in Comparative Example 4 is used instead of the composite solid electrolyte in Example 1.

[0113] Comparative Example 11

[0114] The preparation method and steps are the same as those of Example 5, except that an equal amount of the composite solid electrolyte in Comparative Example 5 is used instead of the composite solid electrolyte in Example 1.

[0115] Comparative Example 12

[0116] The preparation method and steps are the same as those of Example 5, except that an equal amount of the composite solid electrolyte in Comparative Example 6 is used instead of the composite solid electrolyte in Example 1.

[0117] Comparative Example 13

[0118] An all-solid-state lithium battery is prepared by the following preparation method:

[0119] S1. The composite solid electrolyte and polytetrafluoroethylene described in Example 1 were mixed uniformly in a mass ratio of 100:3, and a self-supporting 1.6Li2O·TaCl5·0.2BaTiO3 film (composite solid electrolyte film, thickness of 40 μm) was obtained by shear dispersion and rolling. 0.85 Co 0.05 Mn 0.1 O2 material, polytetrafluoroethylene, acetylene black, and 1.6Li2O·TaCl5·0.2BaTiO3 were mixed in a weight ratio of 82:2:3:13, and a positive electrode film (thickness of 90 μm) was obtained by shear dispersion and roller pressing;

[0120] Using metal magnesium and lithium as raw materials, a lithium-magnesium alloy foil (lithium-magnesium alloy negative electrode) is obtained by melting, cooling and rolling, wherein the lithium content in the lithium-magnesium alloy foil is 80% by mole and the thickness is 40 microns;

[0121] S2. The positive electrode film, the composite solid electrolyte membrane and the lithium-magnesium alloy negative electrode are Figure 1The structures shown are pressed in sequence, and aluminum foil and copper foil collectors are placed on the positive and negative electrode sides respectively. After isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0122] Comparative Example 14

[0123] The preparation method and steps are the same as those in Example 5, except that lithium foil of equal thickness is used instead of lithium-magnesium alloy foil.

[0124] Performance Testing

[0125] 1. Test Method

[0126] (1) Capacity and energy density test: The all-solid-state lithium battery described in the above Example 5 and each comparative example was weighed m0, and charged and discharged at room temperature. It was charged to 4.2V at a constant current of 0.1C, and then discharged to 3V at a constant current of 0.1C (1C is defined as 200mA / g). The discharge capacity Q was recorded. 放 , Q 放 The integrated area in the range of 3 to 4.2 V is recorded as energy E, and the density energy density = E / m0;

[0127] (2) Capacity retention rate test: The all-solid-state lithium battery described in the above Example 5 and each comparative example was charged at room temperature at a constant current of 1C to 4.2V, then charged at a constant voltage at the same voltage to a cut-off current of 0.02C, and then discharged at a constant current of 1C to 3V, and the initial capacity Q0 was recorded. The cycle was repeated in this way. When the cycle reached 100 cycles, the capacity Q1 at this time was recorded, and the capacity retention rate (%) was calculated. Capacity retention rate (%) = Q1 / Q0 × 100%;

[0128] (3) Needle puncture test: The all-solid-state lithium battery described in the above Example 5 and each comparative example is charged at room temperature with a constant current of 1C to 4.2V, then charged at a constant voltage at this voltage to a cut-off current of 0.02C, then discharged at a constant current of 1C to 3V, and cycled for 3 weeks. Then, the all-solid-state battery is charged at a constant current of 1C to 4.2V and pierced with a nail. If it catches fire, it is rejected; if it does not catch fire, it is passed.

[0129] The test conditions in Example 6 are 2-4.3 V, and 1C is defined as 170 mA / g; the test conditions in Example 7 are 2.2-4.6 V, and 1C is defined as 250 mA / g; the test conditions in Example 8 are 3-4.2 V, and 1C is defined as 200 mA / g.

[0130] 2. Test results

[0131] The test results of each embodiment and comparative example are shown in Table 1 and Figure 1 shown.

[0132] Table 1 Experimental data of each embodiment and comparative example

[0133]

[0134] As can be seen from Table 1, the cycle performance of the all-solid-state lithium battery prepared by the composite solid electrolyte provided by the present invention is improved, and the use of lithium alloy as the negative electrode in the all-solid-state lithium battery in combination with lithium phosphotungstate can further improve the cycle stability of the battery. After 100 cycles, the capacity retention rate is not less than 90%, the energy density is not less than 330Wh / kg, and the needle puncture test does not catch fire.

[0135] It can be seen from Comparative Examples 7 to 9 and 12 that if the composite solid electrolyte does not contain BaTiO3 or its content is too low or too high, or is replaced by other substances, the cycle performance of the obtained all-solid-state lithium battery is significantly reduced and the energy density is low.

[0136] It can be seen from Comparative Example 10 that if NbCl5 is used instead of TaCl5 in the composite solid electrolyte, the cycle performance of the obtained all-solid-state lithium battery decreases and the energy density is low.

[0137] It can be seen from Comparative Example 11 that if LiCl is used instead of Li2O in the composite solid electrolyte, the cycle performance of the obtained all-solid-state lithium battery decreases.

[0138] It can be seen from Comparative Examples 13 and 14 that if the all-solid-state lithium battery does not contain an intermediate layer or uses other negative electrodes, the cycle performance of the obtained all-solid-state lithium battery decreases and the safety performance decreases significantly.

[0139] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A composite solid electrolyte, characterized in that: The general formula of the composite solid electrolyte is xLi2O·TaCl5·yBaTiO3, wherein 1≤x≤2, 0.1≤y≤1.

2. The composite solid electrolyte according to claim 1, characterized in that: 1.4≤x≤1.8。 3. A method for preparing a composite solid electrolyte as claimed in claim 1 or 2, characterized in that: The steps include: It is prepared by ball milling Li2O, BaTiO3 and TaCl5.

4. The preparation method according to claim 3, characterized in that: The ball milling time is 5 to 20 hours; the ball milling speed is 300 to 600 rpm.

5. An all-solid-state lithium battery, characterized in that: Comprising the composite solid electrolyte according to claim 1 or 2.

6. The all-solid-state battery according to claim 5, characterized in that: It also includes a negative electrode, an intermediate layer and a positive electrode; the negative electrode is a lithium alloy, and the intermediate layer is lithium phosphotungstate.

7. The all-solid-state battery according to claim 5, characterized in that: The lithium alloy includes one or more of lithium silicon alloy, lithium carbon alloy, lithium silver alloy, lithium boron alloy, lithium tin alloy, lithium magnesium alloy or lithium zinc alloy.

8. The all-solid-state battery according to claim 6, characterized in that: The molar content of lithium in the lithium alloy is 20 to 90%.

9. The all-solid-state battery according to claim 6, characterized in that: The structural formula of the lithium phosphotungstate is Li n PW 12 O 40 , where 2≤n≤3.

10. A method for preparing an all-solid-state battery according to any one of claims 6 to 9, characterized in that: The steps include: S1. Pressing lithium phosphotungstate onto the surface of a lithium alloy to obtain a surface-modified lithium alloy negative electrode; The composite solid electrolyte and the binder are mixed evenly by dry method, and the composite solid electrolyte membrane is obtained by roller pressing; The positive electrode active material, the binder, the conductive agent and the solid electrolyte are mixed evenly by dry method, and the positive electrode film is obtained by roller pressing; S2. The positive electrode film, the composite solid electrolyte membrane, and the surface-modified lithium alloy negative electrode are pressed in sequence, and aluminum foil and copper foil are placed on the positive and negative electrode sides respectively, and an all-solid-state lithium battery is obtained after packaging.